Secrets of WWII: What Really Happened to Rommel? - Rees, Laurence (BBC, 1998)
It is the largest series of its kind ever produced and with recently released secret footage will give the viewer a new insight into the great untold war stories of World War II. In many cases, this new series gives the true stories for the first time this Century. Cracking the engima of one of the most mysterious deaths in the history of Nazi Germany. Did General Rommel really commit a suicide or was he assacinated on Hitler's personal order?